Implementation Of The Police Role In Doing Control And Law Enforcement Against Police In Area Community Organization Indramayu Associated With Act No. 17 In 2013 Jo. Act No. 16 2018 - Sunardi Sunardi; Sri Kusriyah Kusriyah (Jurnal Daulat Hukum, 2018)
In this study the issues to be discussed are: Implementation of the National Police's role in conducting oversight and enforcement of the law against Society. Any barriers faced by the police in doing supervision and enforcement of the law against Social Organization. Police made solutions in overcoming these obstacles above. The methodology used by researchers is the approach empirical juridical, as for sources and types of data in this study are primary data obtained from field studies withway direct communication with the respondent or informant (CJS), And secondary data obtained from the study of literature. Based on the results of research that: the application of the national police role Indramayu in conducting oversight and enforcement of the law against Social Organization that efforts emptive, ie policing effort in order to provide guidance to the public through the development activities of the community that runs from the function Unit Binmas, such as providing information to the public, placement Bhabinkamtibmas in every village one member the Police; Barriers faced is insufficient budget for operations; In the displacement of the secretariat of CBOs, CSOs are rarely reported to the Police Indramayu; Shortage of Human Resources in terms of the establishment of the superintendent; Solutions to overcome these obstaclesthat Bakesbangpol only as a facilitator who records a list of community organizations and in coordination with the central government, while the direct supervision of the CSOs do not have the authority expressly in supervision, coaching, and dissolution of CSOs. Keywords: Implementation; Monitoring; Enforcement; Community Organizations.